Antimicrobial Resistance Patterns of Staphylococcus aureus and Enterococcus Species at the Ethiopian Public Health Institute, Ethiopia: A Five-Year Retrospective Analysis - Abdeta A; Beyene D; Negeri AA (Infection and Drug Resistance, 2023)
Abera Abdeta, Degefu Beyene, Abebe Aseffa Negeri National Clinical Bacteriology and Mycology Reference Laboratory, Ethiopian Public Health Institute, Addis Ababa, EthiopiaCorrespondence: Abera Abdeta, Tel +251911566420, Email aberaabdeta4@gmail.comPurpose: The study aimed to investigate the antimicrobial resistance patterns of Staphylococcus aureus and Enterococcus species isolated from clinical specimens over a period of five years, including resistance to methicillin and vancomycin.Patients and Methods: Bacterial identification and antimicrobial susceptibility testing reports from 2017 to 2021 at the Ethiopian Public Health Institute were used for this retrospective study. The organisms were identified using either BD Phoenix M50, Vitek 2 compact, or conventional biochemical methods, whichever was available at the time of testing. The antimicrobial susceptibility profiles of the isolates were determined using either Kirby-Bauer disc diffusion, BD phoenix M50, or Vitek 2 compact. WHONET software was used to analyze the antimicrobial resistance patterns of both organisms. The p-values of ≤ 0.05 were considered statistically significant.Results: During the study period, a total of 315 Staphylococcus aureus and 92 Enterococcus species were isolated. Out of 315 Staphylococcus aureus isolates, 27% and 5.1% were methicillin and vancomycin resistant, respectively. Staphylococcus aureus showed very high resistance to Penicillin G (86.7%). Out of 92 Enterococcus species recovered, 8.7% were vancomycin-resistant. Enterococcus species showed very high resistance to Penicillin G (71.4%) and tetracyclines (83.3%). Methicillin-resistant Staphylococcus aureus shows 100% resistance to penicillin followed by ciprofloxacin (50%), erythromycin (45.6%), and tetracycline (44.2%) and lower resistance to vancomycin (18.8%). All vancomycin-resistant isolates of both organisms were fully resistant (100%) to all antibiotics tested, except for linezolid and daptomycin, to which they were susceptible.Conclusion: This study found a high prevalence of methicillin and vancomycin-resistant Staphylococcus aureus and vancomycin-resistant Enterococcus species between 2017 and 2021. However, there were no statistically significant changes in the prevalence of these organisms during the study period. This suggests that larger and more representative nationwide data is needed to show trends of these pathogens.Keywords: antimicrobial resistance, Staphylococcus aureus, Enterococcus species, Ethiopia